Model Perkuliahan Daring dengan Mengintegrasikan WhatsApp Group (WaG) dan Google Classroom (GC) - Maskhur Dwi Saputra (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
The impact of Covid-19 has made educational institutions carry out online learning processes; thus, they must provide innovative learning media so that students continue to get material explanations like in face-to-face learning. This study aims to design and evaluate an online lecture model by integrating WaG and GC. Using descriptive method, this study involves Economic Education students at Universitas Indraprasta PGRI for the academic year 2020/2021 who received 276 scientific writing courses. This study consists of (1) designing WaG and GC media, (2) providing the lecture material on the learning media, (3) implementing the media in lecture activities, and (4) evaluating the effectiveness of the media. The questionnaire shows that learning media by integrating WaG and GC is effective to be applied. This is indicated by the percentage of students who strongly agree (54%), agree (32.5%), quite agree (11.2%), disagree (1.6%), and strongly disagree (0.7%). The evaluation includes ease of access, affordability, understanding of the material, two-way communication, media updates, and ease of using technology.